5/-3 x 4 x -2/-9

### 5 Answers | Add Yours

`5/(-3)* 4* (-2)/ (-9)`

` ` `5/(-3)* 4/1* (-2) / (-9)`

` ` `(5*4*-2)/(-3*1*-9)`

`(-40) / 27`

**The solution is `(-40)/27.`**

5/-3*4*-2/-9

=5/-3*4*2/9

=20/-3*2/9

=40/-27=-40/27

5/-3*4*-2/-9=5/-3*4/1*-2/-9

=5*-3*-2/-3*1*-9

=-40/27

=1.48148148

Move the minus sign from the denominator to the front of the expression.

`-5/3 * 4 * -(2)/(-9)`

Move the minus sign from the denominator to the front of the expression.

`-5/3 * 4 * (2/9)`

Multiply `-5` by `4` to get `-20` .

`-(20)/3 * (2/9)`

Multiply all the factors in `-5/3*4*(2/9)`

`(-20 (2/9))/3`

Multiply `-20/3` by `2/9` to get `-40/27`

Thus, the answer is

`-40/27`

`5/-3 xx 4 xx -2/-9= -40/27`

``

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes